Near-infrared mediated tumor destruction by photothermal effect of PANI-Np in vivo - Ibarra, Luis Exequiel (2013)
Photothermal therapy is a therapy in which photon energy is converted into heat to kill cancer. The purpose of this study is to evaluate the in vivo efficacy of photothermal therapy, toxicity and hepatic and renal function of polyaniline nanoparticles (PANI-Np) in a tumor-bearing mice model. The in vivo efficacy of nanoparticles, following NIR light exposure, was assessed by examining tumor growth over time compared to the untreated control. Signs of drug toxicity and the histopathology and morphology of tumor and tissues, after intratumoral injection treatment, were examined or monitored. Excellent photothermal therapy efficacy is achieved upon intratumoral injection of PANI-Np followed by near-infrared light exposure. These results suggest that PANI-Np could be considered as an effective photothermal agent and pave the way to future cancer therapeutics.